Re-envisioning South Omaha urban parks with community diversity in mind - Leise, Katherine Marie (Kansas State University, 2015)
Public parks provide essential green space for people to congregate, exercise, and respite from the city. Urban public parks in the United States began with Frederick Law Olmsted and Calvert Vaux’s Central Park in the mid-1800s (Cranz & Boland, 2004). Since then, planners and designers continue to design urban parks to best serve residents. Therefore, understanding user recreation patterns and preferences is critical for urban park design. Several factors influence leisure styles, including ethnicity, that need to be considered by planners and designers. This study examines parks in South Omaha, Nebraska. Residents living in this area make up over ten different ethnic groups. Notably, Omaha’s largest Hispanic community concentration resides in South Omaha. Through quantitative and qualitative research including site analysis, a literature search, precedent studies, and community interviews, important design considerations emerged. This project presents design considerations and a conceptual redesign for two urban parks in South Omaha: Lynch Park and Spring Lake Park. The designs incorporated the leisure preferences and recreation patterns as revealed through interviews of the majority Hispanic community as well as European, Asian, and African minority ethnic groups. Precedent studies and literature research further informed redesign decisions by providing background knowledge on leisure research, design form, and demographic trends. Nevertheless, urban parks should ultimately respond to the users, regardless of cultural backgrounds, to meet the needs and requirements of all South Omaha residents.
Keywords: Landscape architecture; Urban park design; Community engagement; Ethnic groups; Landscape Architecture (0390); Sociology (0626)